EFEKTIVITAS TEKNIK ANALISIS MANAJEMEN DALAM EVALUASI PROGRAM PENDIDIKAN ISLAM - agus karjuni; Dian Regalistiana; Yuliana Yuliana (Universitas Islam Bunga Bangsa Cirebon, 2026)
Program evaluation in Islamic educational institutions constitutes a critical yet persistently underperforming dimension of educational management, characterized by irregular practice, methodological inconsistency, and an absence of culturally responsive analytical frameworks. While Islamic educational institutions are mandated to conduct systematic program evaluations to ensure continuous quality improvement, evidence indicates that most institutions lack both the technical competency and the conceptual framework to deploy management analysis techniques effectively within their specific institutional contexts. This study investigates the effectiveness of management analysis techniques in the evaluation of Islamic education programs, pursuing three objectives: (1) to analyze the conceptual landscape of program evaluation and its applicability within Islamic educational management contexts, (2) to examine the principal management analysis techniques and their comparative effectiveness for Islamic education program evaluation, and (3) to formulate an integrated model of management analysis-based program evaluation grounded in Islamic values of muhasabah, islah, and hikmah. Employing a systematic library research methodology drawing on thirty-three peer-reviewed sources published between 2020 and 2025, the study proposes the Islamic Program Evaluation Management Framework (IPEMF), an integrated five-technique model that contextualizes established management analysis methods within Islamic educational values and practices.